Comparable perioperative outcomes and mid-term survival in prosthetic valve endocarditis and native valve endocarditis. (2nd May 2018) - Mori, Makoto; Shioda, Kayoko; Nguemeni Tiako, Max Jordan; Bin Mahmood, Syed Usman; Mangi, Abeel A; Yun, James J; Darr, Umer; Pang, Philip Yi Kit; Geirsson, Arnar
Abstract: OBJECTIVES: Cardiac surgery for prosthetic valve endocarditis (PVE) represents one of the highest risk surgeries with in-hospital mortality of 20%. Given the complex nature of the operation, the operative outcome is likely strongly susceptible to the surgeon's experience and centre case volume, as measurements often are not apparent in large observational studies. We sought to evaluate operative outcomes and mid-term survival of patients with PVE compared with those of native valve endocarditis (NVE) at a tertiary care hospital. METHODS: We conducted a single-institutional retrospective review of 188 consecutive patients (146 NVE and 42 PVE) undergoing cardiac surgery for endocarditis between 2011 and 2016 at a tertiary care hospital in the USA. A logistic regression model was fit to evaluate patient characteristics and perioperative outcomes in PVE and NVE: operative mortality and composite events (death, stroke, prolonged intubation, renal failure and sepsis). The Kaplan–Meier analysis was used to estimate the mid-term survival. The Cox proportional hazard model was fit to assess the adjusted risk associated with mid-term survival. RESULTS: Operative mortality was 4.1% for NVE and 0% for PVE ( P = 0.34). Composite events occurred in 30.6% and 38.1% of NVE and PVE, respectively ( P = 0.45). Multivariable logistic regression for composite events showed that PVE was not associated with increased risk of adverse events [odds ratio 1.4, 95% confidence interval (CI) 0.6–3.4; P = 0.49]. The Kaplan–Meier analysis demonstrated no statistically significant difference in survival ( P = 0.99). Finally, the Cox proportional hazard analysis for mid-term mortality demonstrated that PVE was not associated with increased risk for hazard of death: hazard ratio 0.4, 95% CI 0.2–1.1; P = 0.085. CONCLUSIONS: Surgery for PVE can yield a low mortality rate with mid-term survival comparable with those of NVE. The diagnosis of PVE alone should not deter surgeons from operating on this complex patient population, provided that surgical expertise and experienced multidisciplinary team equipped to handle complex clinical scenarios are available.